Potential application of solar water heaters for hot water production in Turkey - Benli, Huseyin (Pergamon-Elsevier Science Ltd, 2016)
Turkey has become one of the fastest growing energy markets in the world in parallel to its economic growth registered in the last 10 years and is rapidly gaining a competitive structure. Turkey is increasingly turning to renewable energy sources as a means to improve its energy security and curb dependence on imported gas from Russia and Iran. Turkey is a country which has the highest hydropower, wind and solar energy potential among European countries. Current energy policy of Turkey primarily aims to maximize solar, geothermal, wind and hydropower potential of the country until 2023. In this study, solar energy potentials of country and solar water heaters were investigated using meteorological and geographical data from six cities in Turkey. Two different collector types were compared in terms of absorber material (galvanized sheet and vacuum tube). The energy requirements for water heating, collector performances, and economic indicators were calculated using climate data. Results showed that galvanized sheet absorbers were the most appropriate in terms of coverage rate of the energy requirements for water-heating across Turkey. The prices of a galvanized absorber type and a vacuum tube heating systems in Turkey are 950 and 1250 USD on average (including installation), respectively. Copper and selective absorber type collectors did not appear to be appropriate based on economic conditions. Six provinces in Turkey were chosen, which were ideally located to take advantage of solar thermal energy and technologies. The data also show that most of the solar water heaters are mainly used by the domestic sector for hot water production (about 96%). The regional popularization analysis indicates that the limited installation of solar water heaters in the Eastern and the Northern district. In these districts, the problem of climatic conditions and lack of purchasing power are addressed. (c) 2015 Elsevier Ltd. All rights reserved.
Keywords: Solar water heater; Renewable energy; Turkey; Potential; Solar Energy